1988
DOI: 10.1007/bf01245144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic haloperidol treatment on peripheral benzodiazepine binding sites in cerebral cortex of rats

Abstract: The effects of 21 days of haloperidol treatment on central benzodiazepine (BZ) receptors in the cerebral cortex of rats and on peripheral-type BZ binding sites (PBS) in the cerebral cortex and heart of rats were studied. Neuroleptic treatment did not affect the maximal binding capacity or the affinity of the central BZ receptor to 3H-flunitrazepam. Chronic haloperidol treatment resulted in a significant increase of 38% in PBS density in the cerebral cortex, with no alteration in PBS density in the heart. No al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…In the present study, we failed to replicate these results, since no regional differences in BDZ V T were observed between patients on or off neuroleptics. Thus our results do not support alteration of BDZ receptors density associated with longterm neuroleptic exposure, a conclusion consistent with preclinical studies (Gavish et al 1988;Giardino et al 1991).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the present study, we failed to replicate these results, since no regional differences in BDZ V T were observed between patients on or off neuroleptics. Thus our results do not support alteration of BDZ receptors density associated with longterm neuroleptic exposure, a conclusion consistent with preclinical studies (Gavish et al 1988;Giardino et al 1991).…”
Section: Discussionsupporting
confidence: 65%
“…Patient clinical evaluation at intake included the Positive and Negative Symptoms Scales (PANS) (Kay et al 1987), a scale that includes the Brief Psychiatric Rating Scale (BPRS) (Overall and Gorham 1962), and the AIMS (Munetz and Benjamin 1988). Since BDZ receptor density is not consistently affected by chronic antipsychotic administration (Gavish et al 1988;Giardino et al 1991), neuroleptic withdrawal was not required for this study.…”
Section: Subjectsmentioning
confidence: 99%
“…Previous studies have demonstrated that repeated CPZ administration can cause an increase in GABA binding in the substantia nigra but not in the striatum (Gale, 1980u,b;Huffman and Ticku, 1983). The lack of effect of chronic CPZ treatment on cortical CBRs, as demonstrated in the present study, is similar to that found in previous studies in which no alteration in r3H]FNZ binding in the cerebral cortex of rats was achieved with chronic haloperidol treatment (Pazo et al, 1987;Gavish et al, 1988).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the [3H]muscimol results, no significant changes were seen in benzodiazepine receptor binding after neuroleptic treatment, thus suggesting the possibility of specific changes at the GABA binding site, but not the benzodiazepine site. The only previous studies that have looked at benzodiazepine receptor binding (using [3H]flunitrazepam) after prolonged neuroleptic treatment reported no alterations in benzodiazepine binding in the cortex or striatum, although a decrease in the cerebellum was found (Rupniak et al, 1987;Gavish et al, 1988).…”
Section: Discussionmentioning
confidence: 92%